Attitudes of healthcare workers at a District in KwaZulu-Natal regarding institutionalisation of antimicrobial stewardship - Andile P. Dlungele; Lehlohonolo J. Mathibe (Southern African Journal of Infectious Diseases)
Background: The Antimicrobial Stewardship (AMS) programme is one of the strategic initiatives of the World Health Organization’s global action plan to reduce antimicrobial resistance (AMR). In sub-Saharan countries, there is insufficient scientific evidence regarding healthcare providers’ perception of institutionalisation of ASPs as a strategy to reduce AMR.